Science and technology indicators by eyes of a librarian - V. S. Lazarev (Библиосфера)
The main directions of the International Conference «STI 2017: Open indicators: innovation, participation and actor-based STI indicators» (Paris, 6-8 September 2017) were the following according to the author's opinion: survey of geographical features, patterns of the science development and a choice of adequate indicators to evaluate these features and patterns; as well as development of new methods for data processing, sharing, analysis and use to assess science and technology. As the conference was held in the format of 4 parallel sessions being carried on simultaneously, the author was compelled to choose the presentations closest to his interests, namely, presentations on scientometrics and related issues. Such a choice was not subjective, because the author being an employee of the Belarusian National Technical University Scientific Library, is engaged in evaluating research activity of scientific organizations and universities (which have long been regarded as an objective of research libraries by serious library specialists of Belarus and Ukraine), as well as of scientific periodicals, and therefore is most interested in information about indicators of research activity of scientific organizations and universities and, especially, about indicators of value and quality of academic periodicals. The presentations that the author has managed to listen to and the discussions that he participated in, transferred via this mini-review seem to be helpful in further bibliometric studies conducted in the Belarusian National Technical University Scientific Library and to be of an interest to the readers of the journal.